An Analysis of Students’ Readiness in Blended Learning Implementation at the Department of English Education of UIN SUSKA Riau - Nurul Fatehha; Zelly Putriani (Indonesian Journal of Integrated English Language Teaching, 2022)
Following the recovery from the COVID-19 Pandemic in 2022, the education system around the world tends to design the most appropriate learning model to ensure the continuity of the education process in the current situation. In this era, blended learning is one of the most popular learning methods to discuss. This method combine online learning and face-to-face learning to maximize learning and teaching to get a deeper understanding. However, before implementing this learning model, it is very necessary to know the students’ readiness first. The student with a high level of readiness is expected to get better learning outcomes. Therefore, this research aimed to know how is students’ readiness for blended learning implementation. This research is quantitative research and in conducting this research, the researcher used a descriptive quantitative survey method as the research design. This research was conducted on October until November 2022 at the Department of English Education of UIN SUSKA Riau. The population of this research is all students batch of 2019, 2020, and 2021 with a total number is 355 students. The researcher took the sample 183 students as the participants by using a simple random sampling technique. To collect the data, the researcher used a questionnaire about students’ readiness in blended learning implementation by Sriwichai (2020) to know how much they are ready for the learning model. The result of this research showed that the student's readiness for blended learning implementation is at “high” category by percentage 66% and followed by 33% of them at the “very high” category for the implementation of blended learning.